PREVALENCE OF BRUCELLOSIS IN BUFFALOES OF BASRA GOVERNORATE, BASRA - IRAQ - Mustafa Q. Hasoon; Mohammed A.Y. Al-Amery (Basrah Journal of Veterinary Research)
The present study was conducted to identify the prevalence of brucellosis among buffaloes in Basra governorate, via examination of serum samples from 250 she buffaloes reared in different Basra reigns. Sera were examined firstly by rose Bengal test (RBT) followed by indirect enzyme linked immunsorbent assay (Elisa). The result of RBT indicated that from 250 buffaloes serum samples there were 27(10.8%) positive against Brucella abortus antigen. Elisa test was performed on 88 sera samples that included a 27 RBT positive sera and other 61 negative sera, and the result revealed that 21( 23.8%) seropositive sera for Brucella abortus. According to the regions of Basra Governorate the percentage rate of brucellosis were indicated in: Al Hartha 6(5,28%) then Al Qurna 5(4,4%), Al Dear 4(3.5), Al Zubair 3(2.6%), Al Medaina 2(1.76%) and Al Tanooma 1(0.88%). More over, infection in older animals found more significant ( P < 0.05) than in youngness, beside that infection rate were high in pregnant buffaloes in compared with non pregnant animals. Conclusion: the brucellosis of buffaloes in Basra governorate were caused by B. abortus and were more prominent in pregnant animals, therefore animals screening of suspected animals was advised,